COMPARATIVE ANALYSIS OF TAKAFUL BUSINESS UNITS AND THEIR PARENT COMPANIES IN INDONESIA THROUGHOUT 2015-2018 USING TWO-STAGE DATA ENVELOPMENT ANALYSIS (DEA) APPROACH - Krisnandhana Zainul, Anggito
Islamic insurance or Takaful is an alternative to conventional insurance that adheres to sharia laws. The Takaful industry is relatively new, but it experienced tremendous global growth annually over the past year. Indonesia is an attractive market for the Takaful industry because of the large number of Muslim populations. Several Takaful firms have established themselves in Indonesia, including Takaful business units. However, conventional insurance firms still dominate the overall insurance market. This research wants to measure the efficiency of the Takaful business units and determine if it is a viable venture for parent companies. Additionally, the research also wants to evaluate the competitiveness of the Takaful business units compared to the parent companies, who provide conventional insurance products, in terms of financial efficiency. The efficiency of the Takaful business units and their parent companies is measured using the Data Envelopment Analysis (DEA). The input variables used in the DEA are Total Asset, Total Expense, and Claim Payment, while the output variables used are Total Revenue and Gross Contributions. This research measured the efficiency of 15 insurance companies and each of their Takaful business units. The variables for the DEA are retrieved from the financial statements of each company from 2015 to 2018. Multiple linear regression is then conducted to determine what variables are significantly correlated to the firms' efficiency. The variables that are tested in the multiple linear regression are the total asset, liquidity ratio, the expense to net premium ratio, and board size. The DEA calculation is the first stage of this research and it showed that the average efficiency score of the Takaful business units is higher than the efficiency of their parent companies. Yuen-Welch's t-test found that the difference between the average efficiency is statistically significant. Therefore, it can be concluded that the Takaful business units are more efficient than their parent companies. The efficiency of Takaful business units is also found to be more stable throughout the research period and consistently outperforming their parent companies. The second stage of this research is conducting the multiple linear regression and it showed that total asset and expense to net premium ratio are negatively correlated to the efficiency of the parent companies, while liquidity and board size are found to be positively correlated. For Takaful business units, total asset and board size are found positively correlated while expense to net premium ratio is negatively correlated. From this finding, the parent companies are recommended to consider downsizing and allocate more resources to their Takaful units to increase the overall efficiency. Additionally, both the Takaful units and their parent companies should increase the size of their corporate board because it is also positively correlated to their financial efficiency.